Implora Cosmetic Purchase: Quality, Brand Image, and Price Impact: Keputusan Pembelian Produk Kosmetik Implora di Sidoarjo: Kualitas, Citra Merek, dan Harga - Sherin Farahdilla; Lilik Indayani (Academia Open, 2024)
This quantitative research aims to examine the influence of Product Quality, Brand Image, and Price on the purchasing decisions of Implora cosmetic products in Sidoarjo. Employing a purposive sampling technique, 100 Implora consumers participated in the study, with data collected through Google Form questionnaires distributed via social media. Utilizing multiple linear regression analysis in IBM SPSS 26, the findings indicate that Product Quality, Brand Image, and Price individually impact purchasing decisions. Moreover, collectively, these factors significantly influence the purchasing decisions of Implora cosmetic products in Sidoarjo. This study contributes valuable insights for marketers and practitioners in the cosmetic industry, emphasizing the importance of product quality, brand image, and pricing strategies in shaping consumer choices. Highlights: Impactful Factors: Explore the individual contributions of Product Quality, Brand Image, and Price on consumer decisions in the cosmetic industry. Quantitative Approach: Employ a robust quantitative methodology, including multiple linear regression analysis, to assess the significance of key variables in the research context. Practical Insights: Provide valuable insights for marketers by emphasizing the collective influence of Product Quality, Brand Image, and Price on the purchase decisions of cosmetic products in a specific market. Keywords: Consumer Behavior, Cosmetic Products, Branding, Pricing Strategies, Purchase Decision